Acceptance of the disease by patients with heart failure - Fraś, Małgorzata; Płatek, Kinga; Sováriová Soósová, Mária; Bąk, Ewelina (Journal of Education, Health and Sport, 2024)
Introduction Nowadays, heart failure is one of the most serious health problems. In Poland, about a million people struggle with it. This is due to several demographic and epidemiological trends, m.in. the improvement of the health care system and the aging of the population. Cardiovascular diseases are a huge challenge for the healthcare system, as they are considered the main cause of death in Poland. The basic assumption of the treatment of the disease includes the improvement of the quality of life Aim of the study: The aim of the study was to assess acceptance of the disease in patients with heart failure receiving outpatient medical care. Material and methods: The research was carried out on a group of 100 patients from NZOZ "Vita". To carry out the research, the author’s questionnaire and the Standardized Questionnaire: AIS and LOT-R were used, and appropriate consents were obtained for their use in the work. Results In the study group, the level of disease acceptance according to the AIS in patients with heart failure treated on an outpatient basis was medium and high (48%; n=48 vs. 48%; n=48). Among the respondents, the largest group (46%; n=46) were people with an average level of optimism according to LOT-R. In people with heart failure, the most common comorbidities were diabetes, hypertension and bronchial asthma. Additional diseases did not have a statistically significant impact on the acceptance of the disease among the examined patients (p>0.05). The importance of religion as well as spiritual development in the respondents’ lives did not influence their acceptance of the disease (p>0.05). Respondents with an optimistic attitude more often represented a higher level of acceptance of the disease according to the AIS than those with a pessimistic attitude (p=0.005). Conclusions Acceptance of the disease is the final stage of adaptation to the disease, it manifests itself in the recognition of limitations and losses that result from the occurrence of a given disease entity. Therefore, accepting the disease brings many benefits that ultimately improve the course of the disease and further prognosis.